2015
DOI: 10.1016/j.jbiomech.2015.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic study of TCPC using in vivo and in vitro 4D Flow MRI and numerical simulation

Abstract: Altered total cavopulmonary connection (TCPC) hemodynamics can cause long-term complications. Patient-specific anatomy hinders generalized solutions. 4D Flow MRI allows in vivo assessment, but not predictions under varying conditions and surgical approaches. Computational fluid dynamics (CFD) improves understanding and explores varying physiological conditions. This study investigated a combination of 4D Flow MRI and CFD to assess TCPC hemodynamics, accompanied with in vitro measurements as CFD validation. 4D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 29 publications
0
35
0
Order By: Relevance
“…Our study, in agreement with Stalder et al ( 17 ), shows that combining 4D CMR and CFD methodologies in a synergistic way can improve the understanding of in vivo hemodynamics. A very recent study ( 18 ) has applied the paradigm of modeling congenital heart disease in vitro and in silico , including 4D CMR, for an interesting case of Fontan circulation (total cavopulmonary connection). This study supports our observations that patient-specific models of congenital defects including 4D CMR allow fine tuning of CFD models, ultimately narrowing the gap for clinical implementation of the numerical models themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Our study, in agreement with Stalder et al ( 17 ), shows that combining 4D CMR and CFD methodologies in a synergistic way can improve the understanding of in vivo hemodynamics. A very recent study ( 18 ) has applied the paradigm of modeling congenital heart disease in vitro and in silico , including 4D CMR, for an interesting case of Fontan circulation (total cavopulmonary connection). This study supports our observations that patient-specific models of congenital defects including 4D CMR allow fine tuning of CFD models, ultimately narrowing the gap for clinical implementation of the numerical models themselves.…”
Section: Discussionmentioning
confidence: 99%
“…This has been done mainly via in vitro models, 9,14,[21][22][23][24][25][26][27][28][29][30][31][32][33][34] CFD models, 3,9,16,17,26,27, and in vivo studies. 10,15,34,[68][69][70] In the past 10 years, growing evidence suggests a relationship between energy loss in the TCPC and Fontan hemodynamics 47,[59][60][61][62]69 and exercise tolerance. 63,66 To date, the influence of energy loss on other well-known complications such as protein-losing enteropathy, plastic bronchitis, or liver fibrosis/cirrhosis has not been studied.…”
Section: The Fontan Proceduresmentioning
confidence: 99%
“…38,44,55,67,90 models still use rigid material and steady inflow conditions. 9,30,34 Recently, a promising in vitro model has been introduced that uses a patient-specific, MRI-derived compliant TCPC model based on the patient-specific compliance value and uses condition-specific (breathheld, free breathing and exercise), real-time, phasecontrast MRI-derived flow waveforms as inflow conditions. 92 First results have shown and quantified the effect of respiration and exercise on energy loss and demonstrated that the effect of these parameters was highly patient-specific.…”
Section: In Vitro Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…4D Flow MRI can capture time-resolved, three-dimensional velocity vector fields within an area of interest. 20,25,39 Previous application of 4D Flow MRI into the realm of cardiovascular diseases such as, congenital heart disease, 19,27 cerebral aneurysm, 10,22,28 and portal hypertension, 26,32 has shown the potential of this technique to directly impact treatment planning. Limitations of 4D Flow MRI are still present: insufficient spatial resolution for accurate assessment of small vessels and slow velocities near the vessel wall, long scan times and high sensitivity to velocity encoding (VENC) settings.…”
Section: Introductionmentioning
confidence: 99%